Gamification of organisations, work, theorisation in the vigorous era of digitalisation - from fading irony and other distance towards a positive reconceptualization of “addiction” - Seppo Poutanen (Estonia, 2022)
This article is speculative in nature. I essentially argue that a key property of effective and successful games, that is their strong addictiveness, has been significantly bypassed in the widespread enthusiasm for digitalisation-boosted gamification of organisations, work and even theoretical thinking. The point of my article is not to claim that the strong associated addictiveness is necessarily something bad, but to provoke unprejudiced reflection on possible features and consequences of the gamification in question, especially in relation to the core of academic work.
34th EGOS Colloquium 2018: Surprise in and around Organizations: Journeys to the Unexpected